ISORA 2016 : Understanding Revenue Administration - Crandall, William Joseph (Departmental Papers; Departmental Paper ;, 2019)
This paper presents the results of the International Survey on Revenue Administration (ISORA) deployed during 2016 and covering fiscal years 2014 and 2015. It is made possible by the participation of 135 tax administrations from around the world that provided data.